2018
DOI: 10.3389/fphar.2018.00593
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Inhibits Mechanical and Thermal Hyperalgesia in a Rat Model of HIV-Induced Neuropathic Pain

Abstract: Aim: In this study, we investigated whether andrographolide (Andro) can alleviate neuropathic pain induced by HIV gp120 plus ddC treatment and the mechanism of its action.Methods: The paw withdrawal threshold and the paw withdrawal latency were observed to assess pain behaviors in all groups of the rats, including control group, control combined with Andro treatment group, sham group, gp120 combined with ddC treatment group, gp120 plus ddC combined with A438079 treatment group, and gp120 plus ddC combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…The inhibitory effect of 78.13 µg/ml HPE was comparable to that of 10 µg/ml ribavirin in vitro , and 480 mg/kg HPE was comparable to that of 60 mg/kg ribavirin in vivo . In the efficacy of antiviral effects, as in the reporting of others herbs (Choi et al, 2016; Sun et al, 2016; Choi et al, 2017; Yi et al, 2018; Luo et al, 2019), the effects of the herbal extract were lower than ribavirin even under several times higher dosage against IBV mRNA level, virus titer, and histopathological injury caused by IBV. However, it is logical since ribavirin is pure compared to the extracts containing many inactive compounds.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The inhibitory effect of 78.13 µg/ml HPE was comparable to that of 10 µg/ml ribavirin in vitro , and 480 mg/kg HPE was comparable to that of 60 mg/kg ribavirin in vivo . In the efficacy of antiviral effects, as in the reporting of others herbs (Choi et al, 2016; Sun et al, 2016; Choi et al, 2017; Yi et al, 2018; Luo et al, 2019), the effects of the herbal extract were lower than ribavirin even under several times higher dosage against IBV mRNA level, virus titer, and histopathological injury caused by IBV. However, it is logical since ribavirin is pure compared to the extracts containing many inactive compounds.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the use of traditional antiviral herbs with no obvious side effects on the human body is still a major focus. Some reports have confirmed that traditional Chinese herbs could effectively inhibit the infection and replication of various viruses (Li et al, 2009; Wang et al, 2015; Choi et al, 2016; Sun et al, 2016; Choi et al, 2017; Yin et al, 2017; Yi et al, 2018; Luo et al, 2019). Hypericum perforatum L. belongs to the genus Guttiferae , which contains approximately 400 species all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge this is the first study to report the expression of Erk1/2 in the CNS after antiretroviral drug treatment. In the periphery, the ratio of p-ERK1/2 to ERK1/2 was increased in the DRG of rats treated with HIV gp120 plus ddC [72]. However, peripheral (intradermal) administration of an Erk1/2 inhibitor was reported to have no effect on ddC-induced mechanical hypersensitivity [11].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several clinical trials demonstrate its positive effects on infectious disease, autoimmune disorders and it has a potential effect against viral defenses [44,50,52]. Moreover, it exerts anti-viral activity towards a number of different viruses including HIV, hepatitis B, herpes simplex, influenza, hepatitis C, chikungunya virus (CHIKV), Epstein-Barr virus (EBV), human papillomavirus (HPV) dengue virus (DENV) and others [51,56,57,[61][62][63][64][65][66][67][68][69][70][71][72]. Recent studies showed that andrographolide is a potential inhibitor of the main protease of SARS-CoV-2 through in silico studies, such as molecular docking, target analysis, toxicity prediction and ADME prediction (absorption, distribution, metabolism, and excretion) [57].…”
Section: Impact Of Andrographolide and Viral Infectionsmentioning
confidence: 99%